If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying q + -6 = 6r + -4p Reorder the terms: -6 + q = 6r + -4p Reorder the terms: -6 + q = -4p + 6r Solving -6 + q = -4p + 6r Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + q = -4p + 6 + 6r Combine like terms: -6 + 6 = 0 0 + q = -4p + 6 + 6r q = -4p + 6 + 6r Reorder the terms: q = 6 + -4p + 6r Simplifying q = 6 + -4p + 6r
| X^2+y^2-8x+7=0 | | 23=-7-6z | | 4=.5(x+3) | | X/8-5/8 | | -17=-16 | | 8+6f=7f-8 | | x-5x+15=0 | | 70+2logX=40 | | 2(2a-b)-6(8b-4a)= | | 2(d+14)=92 | | 19+15h=-9-20+18h | | 1n-1-7n=17 | | 9=(x-600)/10 | | 3/2x+30=60 | | 14.40=8.25+13.5 | | 39=25y+5y | | 8h+8=2+5h | | ln(6-x)-ln(-4-x)=ln(1-8x) | | (ln)x(x+4)=5 | | 1+5y=.75 | | 6-(-4)+8= | | -9+6d=4d+9 | | X^2-7=33-2x^2 | | sqrt(x+16)=(3)sqrt(x) | | 3(w-2)+w=1-2(3-w) | | logx(x+4)=5 | | 9+3x=39xequals | | (3u+6)+u= | | 2w+6s=9 | | 4x-3=97 | | 4w-6=-5+2w | | xy-3yx+7xy-2xy= |